Doppler echocardiographic predictors of low mitral valve area after implantation of one MitraClip: time for a paradigm shift?. (25th November 2020) - Kassar, M; Brugger, N; Seiler, C; Windecker, S; Praz, F
Abstract: Introduction: During edge-to-edge therapy using MitraClip (MC) for severe mitral regurgitation (MR) the interventional cardiologists usually rely on the mean transmitral gradient to decide if they "go for" a second clip in case of suboptimal MR reduction or to stabilise the first MC in the context of prolapse or flail leaflet. The value of this parameter to detect low mitral valve area (MVA) is unknown. Method: During each intervention of the last two years, high quality volumes focused on the MV were acquired. Using a dedicated 3-D analysis software and a new planimetry method, we measured the MVA before and after the implantation of one MC (each orifice was evaluate independently on the most optimal plane). The usual transmitral CW-Doppler parameters (mean gradient (MG), VTI, PHT) were evaluated. Results: We included 120 patients, 69 primary (PMR) and 51 secondary (SMR) mitral regurgitation. For all the parameters, the best model for the curve fitting was y = a + b / x and the two parameters who best correlated with the MVA after MC were PHT (R 2 0.67, p=0.0001) and MG (R 2 0.28, p. 0001). Looking at SMR, the correlation with PHT was even better but there was no correlation with MG. In PMR, the correlation with MG was good but still lower than with PHT (Figure 1). The ROC analysis for PHT showed an AUC of 0.948 and defined an optimal cut-off of 127ms with sensibility and specificity 91% to detect a MVA <2 cm 2 after one MC. Conclusion: The transmitral MG appears as a poor parameter to predict low MVA after the implantation of one MC, especially in SMR probably because in this population the MG depends more on the flow than on the MVA. In the contrary PHT appears as a robust parameter. Funding Acknowledgement: Type of funding source: None